TERRESTRIAL BIOTIC CRISES: PALEOBOTANICAL RECORD AND INTERPRETATION - Krassilov, V.; Shuklina, A. (Bulletin of the Geological Society of Greece, 2007)
The controversial problem of biotic crises is considered in relation to the Cretaceous - Tertiary and Permian - Triassic transboundary events in the nonmarine sequence of Far East and the Russian platform, respectively. In both cases, the floristic changes across the critical boundaries proceeded in few steps, none of which indicated a catastrophic destruction of plant communities. Rather the vegetational changes were related to a spread of continental climates, downslope migrations of altitudinal belts and deciduousness. Neither the end-Permian "fungal spike", nor the end-Cretaceous "fern spike" are supported by paleobotanical evidence. Incidentally, an increase of ferns in the transboundary plant-bearing sequences can be explained, upon the recent examples, by the rapid fern growth on the ash fallouts. A model of biotic crises is proposed, in which the intracratonic rifting and trap magmatism are causally related to the rise/spheric expansion of continental crust. A concerted impact of environmental changes was manifested at the beta level diversity in the first place, e.g. the reduction of wetlands and eutrophication of aquatic ecosystems, with a consequential loss of their alpha diversity